A Case of Gitelman Syndrome; Incidentally Diagnosed in Elderly - Selma KARAAHMETOĞLU; Mehmet Veysel COŞKUN (Bezmiâlem Science, 2022)

(untitled)
Gitelman syndrome is an autosomal recessive renal tubular disease that is followed by symptoms, such as fatigue, muscle weakness, tetany, polydipsia, and nocturia. Additionally, hypokalemia, hypomagnesemia, and hypocalciuria are observed and it is usually diagnosed in adulthood but some cases are coincidentally diagnosed in the elderly. Herein, we had a 60-year-old female patient who was incidentally found to have hypokalemia and then diagnosed with Gitelman syndrome by furosemide loading test and SCL12A3 gene mutation detection.